Peranan Etika dan Komitmen Organisasi dalam Budgetary Slack - Menhard Menhard; Safrizal Safrizal (Journal on Education, 2023)
Budgeting is an obligation for organizations in carrying out their operations, this study aims to look at the role of ethics and organizational commitment to budgetary slack. This research is quantitative with primary sources through questionnaires and secondary through library research. The location of this research is the Pekanbaru City Regional Apparatus Organization (OPD), the population of all employees at the Kuantan Singingi OPD and with a purposive sampling method through the criteria of All OPDs in the Pekanbaru City Government and echelon 3 and 4 officials because they have worked for at least 1 year, are considered to have experience and already know the conditions of development in the Pekanbaru City OPD which consists of the Head of the OPD, the Head of the Finance Section, and the Head of the Program Section who are assigned to the Pekanbaru City Regional Government Agencies from 43 OPD. The results of this study indicate that ethics has an important role in budgetary slack, in addition to organizational commitment it also influences budgetary slack..